Using Phenomenography to compare the variation of language teachers and learners’ attitudes towards Computer Assisted Language Learning - Zaphiris, Panayiotis; Kyriacou, Stelios; Papadima-Sophocleous, Salomi; Parmaxi, Antigoni; Stylianou, Kostas (My University, 2013)
The increasing use of new technologies in the language classroom is constantly altering the way teachers and learners experience language learning and teaching. The new possibilities that technologies bring into the language classroom need to be further examined primarily by exploring the ways in which learners and language instructors ascribe meaning to Computer Assisted Language Learning (CALL). This paper focuses on presenting the main findings of a qualitative study using a phenomenograpic approach to investigate how language teachers and learners experience, understand and ascribe meaning to CALL. The phenomenographic approach is adopted since it can richly describe the object of study by emphasising the variation in the meaning that is found in the participants’ experiences of the phenomenon. More specifically, the study focuses on exploring learners’ and teachers’: a) range of conceptions for CALL, and b) attitudes towards the use of technological means in language learning. Briefly, students and teachers’ approaches and attitudes towards CALL are analyzed separately in order to comparatively examine their views and provide constructive feedback to enhance the learning process.
Keywords: Phenomenography; Teacher attitudes; Students attitudes; CALL ignorance; CALL awareness